Circular Economy-Based Waste Management in Tomohon City: Toward a Green Economy through Innovative and Participatory Approaches - Elsje Hanna Lintong; Deisy Agnes Pertiwi Juita Pangkey; Hendry C.M. Runtuwene (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to identify the potential for implementing a circular economy in waste management in Tomohon City as an effort to support the transition toward a green economy. A descriptive qualitative approach was employed, using field observation, in-depth interviews with environmental and economic actors, and policy document analysis. The research was conducted in strategic locations such as the Final Disposal Site (TPA), traditional markets, waste banks, and tourist destinations that serve as centers of community activity and tourism. Findings show that the current waste management system in Tomohon still follows a linear model, resulting in significant environmental pressures. However, local initiatives such as plastic recycling by MSMEs, organic composting, and active participation in waste banks provide early indications of successful circular practices. Nevertheless, scalability and integration of these models into the regional economy remain limited due to infrastructure constraints, technical capacity, and weak policy coordination. Based on these findings, recommendations include the need for investment in waste processing infrastructure, institutional strengthening of waste banks, formulation of local policies oriented toward circular economy principles, and increased community participation through education and economic incentives. With the implementation of these recommendations, Tomohon has the potential to become a model for sustainable waste management based on the circular economy in Indonesia’s mountainous urban regions.